2022
DOI: 10.3389/falgy.2022.806391
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th17 Cytokines in Airway Remodeling in Asthma and Therapy Perspectives

Abstract: Airway remodeling is a frequent pathological feature of severe asthma leading to permanent airway obstruction in up to 50% of cases and to respiratory disability. Although structural changes related to airway remodeling are well-characterized, immunological processes triggering and maintaining this phenomenon are still poorly understood. As a consequence, no biotherapy targeting cytokines are currently efficient to treat airway remodeling and only bronchial thermoplasty may have an effect on bronchial nerves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 221 publications
(305 reference statements)
0
6
0
Order By: Relevance
“…The pro-inflammatory role of TGF-β in established asthma may be related to asthma highly inflammatory environment that includes high concentrations of IL-6 and IL-21 ( 152 ), which in mice induce Th17 differentiation in the presence of low levels of TGF-β ( 31 , 153 ) (in human, the presence of IL-1β is also required ( 32 )). Th17 cytokines, including IL-17, play a role in neutrophilic inflammation in severe asthma ( 154 ) and IL-21is increased in human asthmatic airways ( 155 ). In the early stage of asthma, the concentrations of IL-6 and IL-21 are likely insufficient to induce Th17 differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-inflammatory role of TGF-β in established asthma may be related to asthma highly inflammatory environment that includes high concentrations of IL-6 and IL-21 ( 152 ), which in mice induce Th17 differentiation in the presence of low levels of TGF-β ( 31 , 153 ) (in human, the presence of IL-1β is also required ( 32 )). Th17 cytokines, including IL-17, play a role in neutrophilic inflammation in severe asthma ( 154 ) and IL-21is increased in human asthmatic airways ( 155 ). In the early stage of asthma, the concentrations of IL-6 and IL-21 are likely insufficient to induce Th17 differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…First, we demonstrated that the presence of an eosinophilic infiltrate in the interstitial, perivascular and peribronchiolar regions of the lung and high IgE/IgG1 levels may favor increased Ahr and the initiation of lung remodeling, leading to the production of pro-fibrotic Th2 cytokines or other mediators responsible for the greater deposition of ECM components, such as collagen. Furthermore, the concurrent neutrophilic infiltration of the lungs associated with interconnected mechanisms, such as IL-17A, IFN-γ and IgG2a, indicates that neutrophil-rich inflammation was also driven by Th1/Th17 cells [ 28 , 33 ], relevant in the context of remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of type 2-low asthma is not completely elucidated, the following mechanisms have been suggested to play a role in this subtype of asthma: (i) type 1 (IFN-mediated) and type 3 (IL-17-mediated) immune pathways together with airway neutrophilia; (ii) pauci-granulocytic mechanisms; (iii) systemic inflammation associated with IL-6, obesity, and metabolic dysfunction [ 32 ]. In particular, murine models show that IL-17 contributes to neutrophilic airway inflammation, bronchial hyper-responsiveness, mucus hypersecretion, airway obstruction, and corticosteroid resistance [ 33 , 34 , 35 ]. In addition, levels of Th17-derived IL-17 in the airway and peripheral blood correlate with disease severity [ 34 , 36 ].…”
Section: Eosinophils and Bronchial Asthmamentioning
confidence: 99%